Safe Havens - Skyddade platser på fartyg i Arktis - Birging, Tobias; Feurst, Filip (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2013)
The Arctic is considered to contain the last parts of pristine marine environments on earth. The climate change during the recent years, which has increased the accessibility to the area, has resulted in a major commercial interest. An increased presence of vessels increases the risk of accidents, with consequences for both human life and environment. The lack of infrastructure and the fragile environment of the area places special demands on the operations conducted there, which drives the development of new rules and guidelines. This study aims to seek answers to the ability to apply existing methods of assistance and rescue upon vessels, thereby increase the safety for human life and environment in this sensitive area. The base of this study is a literature survey. A questionnaire where utilized and interviews with experts were conducted. The study shows that the existing rules and guidelines provide the ability for increased safety. The remoteness and poor infrastructure pose challenges to commercial activity in general, but to rescue and relief operations in particular. Based upon existing and proposed maritime rules and guidelines, conditions to increase the safety for human life and environment exist.